Levels and trends of older adult mortality in Sub-Saharan Africa : comparison of sources and estimates - (:unkn) unknown (My University, 2022)
Since independence, efforts to reduce mortality have focused on child and maternal mortality, which is considered too high. Subsequently, analyses of maternal mortality have been extended to adults in general (15 to 50 or even 60 years old). Beyond these ages, mortality studies remain poorly documented due to the lack of adequate civil registration. The numerous errors in age are sources of bias and make it difficult to produce estimates. The aim of this doctoral dissertation is therefore to contribute to improving the state of knowledge on the mortality of adults aged 50-79. The option of restricting the analyses to the under-80s is intended to limit the effect of age errors which can be extreme at very old ages. Starting with a review of existing methods, we examine the extent to which a judicious use of these methods can make it possible to estimate the levels and trends of mortality in older adults by exploiting different sources (censuses, household sample surveys, population surveillance systems) available for several countries in the sub-Saharan region.
Keywords: African Research